Analysis on anonymity and regulation of digital currency transactions based on game theory - Xian ZHANG; Jianming ZHU; Zhiyuan SUI; Shengzhi MING (网络与信息安全学报)
By using technologies such as blockchain, digital currency, as a new type of monetary asset, has been promoting the development of digital economy.Digital currency trading platform plays an important role in the use of private digital currency by digital currency users.Existing digital currency trading platforms may expose users’ privacy and provide illegal elements with the conditions to participate in various abnormal trading behaviors such as“air dropping” events, extortion, fraud, etc.The strong anonymity protection of users by digital currency trading platforms also make it more difficult for regulatory authorities to supervise digital currency transactions.Therefore, the strength of the anonymity protection of users by digital currency trading platforms need to consider not only the privacy protection of users, but also meet the regulatory requirements.For this reason, based on the analysis of the relationship between the digital currency trading platforms and the supervisory departments, an evolutionary game model was established, the digital currency trading platform and the supervisory game model were defined and constructed, and the replication dynamic equation was solved and the balanced solution was obtained according to the income matrix between the digital currency trading platform and the supervisory department.By building a Jacobian matrix, the stability of the evolutionary system under different parameters was analyzed.Besides, the evolutionary stable selection and strategy of the digital currency trading platform and the regulatory authority under different conditions were also analyzed.With Matlab, different strategies of anonymity protection of the digital currency trading platform and different strategies of supervision strategy of the regulatory department were simulated to verify the accuracy of the game model.Based on the results of the simulations, some suggestions on the supervision of digital currency trading platforms are put forward, which provides a theoretical basis for the future supervision of digital currency trading platforms in China.